2017
DOI: 10.1007/s40368-017-0286-8
|View full text |Cite
|
Sign up to set email alerts
|

Maternal identification of dental caries lesions in their children aged 1–3 years

Abstract: Mothers of children aged 1 year old identified dental caries at initial and established/severe stages. Mothers of children aged 2 and 3 years identified dental caries only at established/severe stages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…This study also suggests barriers to lack of early dental visits are predominantly related to poor oral health literacy. As early dental carious lesions present with subtle clinical signs and mild symptoms, non‐clinicians will find them difficult to detect and parents may under‐estimate dental disease 17 . By the time symptoms manifest or cavitation is evident, and parents become aware of dental problems, the window of opportunity for prevention may be greatly diminished.…”
Section: Discussionmentioning
confidence: 99%
“…This study also suggests barriers to lack of early dental visits are predominantly related to poor oral health literacy. As early dental carious lesions present with subtle clinical signs and mild symptoms, non‐clinicians will find them difficult to detect and parents may under‐estimate dental disease 17 . By the time symptoms manifest or cavitation is evident, and parents become aware of dental problems, the window of opportunity for prevention may be greatly diminished.…”
Section: Discussionmentioning
confidence: 99%
“…Studies differed in their grouping of caries scores. For example, nine different caries surfaces measures and seven caries teeth measures were identified in this review. Some studies grouped them to classify caries as dentin and enamel lesions while others classified them as initial/early, moderate/established and severe/extensive lesions .…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al [ 7 ] found that dental visits, brushing frequency, lower parental perceived importance of baby teeth, and weaning onto solids are determinants associated with plaque accumulation, validating these results specifically in children. In the work of Fernandes et al [ 8 ], a cross-sectional study of 274 children and their mothers based on demographic/socio-economic status is presented; through a Poisson regression approach, an analysis was performed, obtaining that dental caries can be mainly found in mothers of children aged 1, demonstrating the relationship between demographic/socio-economic status and caries.…”
Section: Introductionmentioning
confidence: 99%